Challenges in Implementing School Vision and Mission in Riau Islands - Nurhayati Nurhayati; Juni Mahanis; Enik Nurfaizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to identify and analyze the challenges faced by schools in the Riau Archipelago in implementing their vision and mission. School vision and mission are crucial guidelines in the educational process, as they reflect the goals and direction that the educational institution seeks to achieve. However, the challenges in their implementation often affect the effectiveness of achieving those goals. This study focuses on local factors that may influence the implementation of school vision and mission in the Riau Archipelago, such as limited resources, infrastructure issues, and cultural and social barriers in the archipelago region. The methodology used in this study is descriptive qualitative, with data collection techniques through in-depth interviews, field observations, and documentation studies. The results of the study indicate that, although the vision and mission of schools in the Riau Archipelago are clear and well-defined, the main challenges lie in the lack of adequate facilities and resources, as well as difficulties in reaching remote and isolated areas. Additionally, local cultural factors and public perceptions of education also affect effective implementation. This study suggests the need for improved access to educational resources, training for teachers and school principals, as well as the utilization of technology to overcome geographical and social barriers. Therefore, this study is expected to contribute to the improvement of the education system in the Riau Archipelago and other remote areas